TOXICITY STUDY OF ATRAZINE AND METHYL PARATHION IN POTENTIAL FUNGI SPECIES - Chee, Loke Jeen (2018)
Pesticides are abundantly used for prevention of pests harming and affecting the yield of crops, such as atrazine and methyl parathion. However, overly used of pesticides led to accumulation of pesticides in soil and drinking water which result in severe impacts on human’s health. Hence, human need to find out better remediation strategies to reduce the pollutants. In this research, mycoremediation is introduced to remediate the pollutants because it breakdown the pollutants using fungi which is an environmental friendly and cost-effective way. Objective of this research is to find out the potential fungi species that can remediate atrazine and methyl parathion based on their tolerance level against toxicity of atrazine and methyl parathion. First, 11 types of random fungi were used for screening test in PDA. After screening test, 8 selected fungi species were carried on the experiment with toxicity testing of potential fungi species in different concentration of the pesticides respectively. In toxicity test, fungi species were selected for potential fungi species because it can grow well and consistent in different tested concentrations. As result, Trichoderma erinaceum (I-2), Aspergillus nidulans (I-8) and P. simplicissimum (I-19) were determined to have potential to remediate atrazine with the highest mean dry mass in highest tested concentration of 20 ppm which is 0.116g, 0.073g, and 0.053g respectively. In another hand, Penicillium chrysogenum (I-1), Trichoderma erinaceum (I-2), Aspergillus nidulans (I-8) and Aspergillus niger (I-26) were determined as potential fungi species to remediate methyl parathion with the highest mean dry mass in highest tested concentration of 40 ppm which is 0.140g, 0.076g, 0.143g, and 0.163g respectively.